Pengembangan Media Pembelajaran Snake and Ladders Culture pada Materi Indonesiaku Kaya Budaya Kelas IV SD Negeri 3 Tambaksogra - Berlian Sabrina; Agung Nugroho (Departement of Mathematics Education, 2024)
A teacher's success in creating an engaging learning environment and fostering positive student attitudes is significantly influenced by various factors, including using interesting learning media. Engaging learning media can make the learning process more active and interactive. This study aims to develop and evaluate the feasibility of the Snake and Ladders Culture learning media for